2000
DOI: 10.1046/j.1432-1327.2000.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of silicatein and collagen genes in the marine sponge Suberites domuncula is controlled by silicate and myotrophin

Abstract: The major skeletal elements in the (Porifera) sponges, are spicules formed from inorganic material. The spicules in the Demospongiae class are composed of hydrated, amorphous silica. Recently an enzyme, silicatein, which polymerizes alkoxide substrates to silica was described from the sponge Tethya aurantia. In the present study the cDNA encoding silicatein was isolated from the sponge Suberites domuncula. The deduced polypeptide comprises 331 amino acids and has a calculated size of M r 36 306. This cDNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
299
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(309 citation statements)
references
References 34 publications
10
299
0
Order By: Relevance
“…In the present study we found that the total extract as well as the extract from separated lamellae of these spicules contains a silicatein(-related) molecule, with respect to size, post-translation modification and enzyme activity. SDS-PAGE showed that characteristic lowmolecular mass protein(s) of 27·kDa exist in the spicules, which match in size with silicateins from demosponges (Cha et al, 1999;Krasko et al, 2000;Müller et al, 2007a) and correspond to the mature enzyme. As known from the different forms of the silicateins in T. aurantium (Cha et al, 1999) or S. domuncula (Krasko et al, 2000;Müller et al, 2003), these molecules are expressed/translated as a pro-enzyme (signal peptide-propeptidemature enzyme: 36.3·kDa) and processed via the 34.7·kDa form (propeptide-mature enzyme) to the 23·kDa mature enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study we found that the total extract as well as the extract from separated lamellae of these spicules contains a silicatein(-related) molecule, with respect to size, post-translation modification and enzyme activity. SDS-PAGE showed that characteristic lowmolecular mass protein(s) of 27·kDa exist in the spicules, which match in size with silicateins from demosponges (Cha et al, 1999;Krasko et al, 2000;Müller et al, 2007a) and correspond to the mature enzyme. As known from the different forms of the silicateins in T. aurantium (Cha et al, 1999) or S. domuncula (Krasko et al, 2000;Müller et al, 2003), these molecules are expressed/translated as a pro-enzyme (signal peptide-propeptidemature enzyme: 36.3·kDa) and processed via the 34.7·kDa form (propeptide-mature enzyme) to the 23·kDa mature enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The responsible enzyme, silicatein, was first described by the group of Morse in the marine demosponge Tethya aurantium (Cha et al, 1999) and subsequently also identified in other demosponges, most prominently in Suberites domuncula (Krasko et al, 2000). The genes of two isoforms of silicateins, silicatein-␣ and silicatein-␤ (Cha et al, 1999), have been identified in marine demosponges, and a third type, silicatein-␥, has been identified but not yet at the gene level (Shimizu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The center of these spicules is formed by an axial canal which contains an axial Wlament (Kaluzhnaya et al, 2005a) composed of silicatein (Kaluzhnaya et al, 2005b), the enzyme that is involved in the polymerization of silica (Cha et al, 1999;Krasko et al, 2000). An earlier study with the sponge Tethya aurantium (Weaver and Morse, 2003) reported that bifurcation of the axial Wlament precisely results in an unusual dichotomous morphology of the spicules.…”
Section: Discussionmentioning
confidence: 99%
“…Silicatein belongs to the family of cathepsin L proteases (Cha et al, 1999) and is involved in the condensation/polymerization reaction of silica (Cha et al, 1999;Krasko et al, 2000).…”
Section: Introductionmentioning
confidence: 99%